Formation of spring rape yield depending on fractional composition of seed material - П. С. Вишнівський; І. М. Катеринчук (Plant Varieties Studying and Protection)
Purpose. To study the influence of fractional composition of seed material on productive properties of spring rape seeds of the ‘Magnat’ variety and ‘MVM’ (‘Gladiator’) variety sample. Methods. Field investigations, laboratory tests, statistical analysis. Results. During 2013–2014, the influence of sown seeds of different size fractions (up to 2,5 g; 2,6–3,5 g; 3,6 g and more) on the indices of productivity of spring rape varieties was studied. It was found that over the years of study field germination of sown fractions of seeds in ‘Magnat’ variety averaged 83.5%, in ‘MSM’ variety sample – 86.7%. During the periods of seedling emergence and harvesting, the density of spring rape crops varied depending on relevant fraction of sown seeds. In the ‘Magnat’ variety, photosynthetic potential of crops ranged from 1.1 to 1.3 million m2/ha, in ‘MSM’ variety sample – from 1.2 to 1.6 million m2/ha. Depending on the seed fractions applied, ‘Magnat’ variety crops during the growing season accumulated organic biomass from 2.05 to 2.36 g/m2 per day, ‘MSM’ sample variety – from 1.83 to 2.10 g/m2 per day. Conclusions. It was established that different fractions of spring rape seeds sown in the Northern Forest-Steppe zone of Ukraine affected the indices of germinating energy and laboratory germination, crop density formation, leaf surface area and intensity of photosynthesis process (crop photosynthetic potential, net photosynthesis performance). The highest indices of productivity and yield in the ‘Magnat’ variety was ensured by large-seeded fraction (3,6 g and more), in the ‘MVM’ (‘Gladiator’) sample variety – by small-seeded fraction (up to 2,5 g).